2003
DOI: 10.1002/pssb.200301659
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of non‐adiabatic small polaron hopping conduction in Bi0.1A0.9MnO3 (A = Ca, Sr, Pb)

Abstract: A detailed study of the electrical transport properties of semiconducting perovskites Bi 0.1 A 0.9 MnO 3 (A = Ca, Sr, Pb of increasing ionic radius r i ) have been made over a wide range of temperature 80 -375 K. XRD studies indicate a change of structural differences with change of ionic radius r i of A. The dc conductivity of the Sr-and Pb-doped samples with larger r i is much lower than that of the Ca-doped sample of smaller r i . Unlike the Sr-and Pb-doped samples, little negative magnetoresistance is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
(51 reference statements)
2
11
0
Order By: Relevance
“…There is a decrease in volume similar as reported by W. Boujelben et al [1]. Although Bi 3+ (1.17 Å) ion has larger ionic radii than Pr 3+ (1.126 Å) ion with coordination VIII, hence increase in volume may be ascribed due to the presence of magnetic polarons originated as a result of the competing behavior of larger ionic radii generated ferromagnetic-DE and charge order state of the end compound BiSrMnO 3 compound [17][18][19]. The calculated lattice parameters (a, b and c) and unit cell volume with fitting reliability parameter are listed in Table 1.…”
Section: Crystal Structuresupporting
confidence: 70%
See 1 more Smart Citation
“…There is a decrease in volume similar as reported by W. Boujelben et al [1]. Although Bi 3+ (1.17 Å) ion has larger ionic radii than Pr 3+ (1.126 Å) ion with coordination VIII, hence increase in volume may be ascribed due to the presence of magnetic polarons originated as a result of the competing behavior of larger ionic radii generated ferromagnetic-DE and charge order state of the end compound BiSrMnO 3 compound [17][18][19]. The calculated lattice parameters (a, b and c) and unit cell volume with fitting reliability parameter are listed in Table 1.…”
Section: Crystal Structuresupporting
confidence: 70%
“…Larger ionic radii of Bi 3+ ion supports DE conduction mechanism, hence resistivity decrease for x < 0.20 doping concentration. For x > 0.20, the charge ordered state of end Bi 1−x Sr x MnO 3 (BSMO) compound starts dominating [18,19]. As a result competition between DE and charge ordered state, resistivity increases and a peak generates in low temperature regime [20].…”
Section: Resistivity Measurementmentioning
confidence: 97%
“…The Mö ssbauer spectroscopy study confirmed the variance in the surrounding of Fe [23,27,28,38,39]. It would be noticed that two relaxation processes occurred also in the non-doped Bi 12 MnO 20 -BiMn 2 O 5 self-composite [12].…”
Section: Electric Propertiesmentioning
confidence: 52%
“…It should be noted that several compounds containing Mn ions show polaronic conduction [12,23,24,27,28,38,39]. There are two models of small polaron conductivity, which include the potential energy landscape determined by the degree of crystal lattice disorder [25,26].…”
Section: Electric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation